Nano-crystallisation and magnetic softening in Fe–B binary alloys induced by ultra-rapid heating. (5th September 2018) - Parsons, R; Zang, B; Onodera, K; Kishimoto, H; Shoji, T; Kato, A; Suzuki, K
Abstract: Magnetically soft nanostructures are known to be prepared by the primary crystallisation of Fe-based amorphous precursors containing Cu and/or Nb. These nonmagnetic additives are essential for accelerated nucleation and retarded crystal growth during crystallisation. However, it has recently been found that none of these additives are necessary for the preparation of similar nanostructures when ultra-rapid annealing (URA) is employed. As a result, a magnetically soft nanostructure with exceptionally high Fe contents is realized in a simple Fe–B binary system. An obvious question is the mechanism of the nanostructural formation in such a simple system. To answer this question, the crystallisation behaviour of amorphous precursors was investigated by means of in situ resistivity measurements with heating rates up to ~100 K s −1 . The primary crystallisation temperature ( T p ) in Fe86 B14 is increased at least by ~100 K under URA. This brings T p to the vicinity of the glass transition ( T g ) predicted by Egami's zeroth-order approximation, suggesting that an enhanced nucleation rate near T g due to the contribution of homogeneous nucleation could be responsible for the nanostructural formation in Fe86 B14 . Contrarily, the effect of URA is absent from Fe80 B14 Nb6, and a magnetically soft nanostructure is realized by conventional annealing because the crystallisation reaction in this alloy takes place above T g even with a low heating rate of ~1 K s −1 . URA offers new possibilities for enhancing the saturation magnetization in nanocrystalline soft magnetic alloys through reductions of the amount of nonmagnetic additives.